2012
DOI: 10.1029/2011jc007494
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the effects of mangrove areas and tidal flats on tides: A case study of Darwin Harbour, Australia

Abstract: [1] The tidal dynamics of Darwin Harbour, Australia, are simulated using a finite volume coastal ocean model. The calibrated model agreed well with the observed sea surface elevation and current velocity. Results indicate that the harbor's hydrodynamics are driven mainly by the tides, with wind and river inputs playing only small roles. The M 2 tide is dominant, with amplitude 1.7 m and peak current speed 3.0 m s À1 . Sensitivity tests using the model indicate that the mangrove areas and tidal flats play cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 18 publications
(22 reference statements)
2
37
0
Order By: Relevance
“…The strong tidal currents in combination with the complex, shallow bathymetry caused the high spatial variability observed in most of the surface measurements from site to site (e.g., Figure 2) as a result of localized, small scale up-and downwelling processes. Previous modeling studies have shown that Darwin Harbour's hydrodynamics are driven mainly by tides, with the wind and seasonal river inputs playing somewhat smaller roles (Li et al, 2012). In particular, Li et al (2014) reported that the dynamics of TSS in DH vary with the spring-neap tidal cycle, with the whole water column being well-mixed during spring tides.…”
Section: Effect Of Local and Seasonal Forcingmentioning
confidence: 99%
“…The strong tidal currents in combination with the complex, shallow bathymetry caused the high spatial variability observed in most of the surface measurements from site to site (e.g., Figure 2) as a result of localized, small scale up-and downwelling processes. Previous modeling studies have shown that Darwin Harbour's hydrodynamics are driven mainly by tides, with the wind and seasonal river inputs playing somewhat smaller roles (Li et al, 2012). In particular, Li et al (2014) reported that the dynamics of TSS in DH vary with the spring-neap tidal cycle, with the whole water column being well-mixed during spring tides.…”
Section: Effect Of Local and Seasonal Forcingmentioning
confidence: 99%
“…Changes in the SuspendedSediment Distribution The removal of the mangroves and tidal flats changes the tides in the harbor [Li et al, 2012], and consequently generates a different SSC distribution. In Experiment 2, with the mangrove areas removed from the model, the water was still turbid in the outer harbor, as in Experiment 1, during both spring tides ( Figure 9a) and neap tides ( Figure 9b); however, the maximum SSC at the bottom level was about 20% larger than in Experiment 1.…”
Section: Effect Of Mangroves and Tidalmentioning
confidence: 99%
“…Similar effects appeared in the Middle Arm entrance (Cross-section 4), as shown in Figures 10g-10i. Similar to Li et al [2012], the combined mangrove areas and tidal flats were removed incrementally by 30%, 50%, and 70% in Experiments 4-6 to further examine their impact on total sediment flux in the harbor. The total sediment flux at Cross-section 1, seaward in Experiment 1 with the mangrove areas and tidal flats present, decreased in Experiment 4 (30% removal), then slightly increased in Experiment 5 (50% removal) (Figure 11).…”
Section: Factors Controlling Suspended-sediment Transportmentioning
confidence: 99%
See 2 more Smart Citations